Incidence of Early Complications in Laparoscopic Total Thyroidectomy Vs Open Thyroidectomy Using Breast Approach in Simple Multinodular Goiter (Medico Legal Update, 2020)
Total thyroidectomy is a popular and common surgical operation in the word. it’s done through collar incision that may culmination with bad cosmetic appearance for this type of wound in the neck. Recently laparoscopic total thyroidectomy was become popular in experience laparoscopic hand surgeons. Among patients, we noticed many early complications that may occur after laparoscopic total thyroidectomy due to a new technique in total removal of thyroid gland to give an excellent cosmetic result. In our study we want to do comparative study for incidence of early complication (which occur within early 30 postoperative day) between LTT (laparoscopic total thyroidectomy) and OTT (open total thyroidectomy). The prospective study done to 122 patients who mad total thyroidectomy for simple multinodular goiter. 58 patients underwent LTT and 64 patients OTT in GIT center in Thi-Qar city which are done by the same surgeon for all patients. study done through 2 years 1/5/2017 till 30/4/2019 through breast approach and collar incision. Surgical outcome records the complications that occur to the patients within 30 days post-operatively. The main age of patients in LTT was 39.6 ± 6.4 and in OTT was 48.2±8 (p= 004). The operating time in LTT 125.4± 4 minutes while in OTT was 92.6± 2 (p=0.03). There were no significant differences in hospital stay in both groups. patients with OTT experienced more pain than ETT group postoperatively as evaluated by a visual analog scale. Cosmetically group LTT were very satisfied with this procedure according to the questionnaire we used. The fallow up period was 30 days only. most of early complications are no significant differences between 2 groups as the LTT done by experience laparoscopic hands. 2 cases (3.5%) only were convert to open procedure. Conclusion: LTT procedure is a new technique used to give an excellent cosmetic result rather than used collar incision in the midline of the neck, there are no significant differences in all early complications that may occur in LTT and OTT. LTT must be done by an experience laparoscopic hand.